IDENTITAS SAYYID DAN LEGITIMASI SOSIAL DI CIKOANG, SULAWESI SELATAN: PERSPEKTIF WEBER DAN BOURDIEU: A Weberian–Bourdieusian Analysis of Sayyid Identity and Social Legitimacy in Cikoang, South Sulawesi - Asma Dwi Putri; Wahyu Pratiwi (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2026)
This study examines the social legitimacy of the Sayyid community in Cikoang, South Sulawesi, through the perspectives of Max Weber and Pierre Bourdieu. Using a qualitative interpretive approach, data were collected through in-depth interviews with twelve informants selected through purposive sampling and analyzed using reflexive thematic analysis. The findings show that Sayyid legitimacy is sustained not only through genealogical claims as descendants of the Prophet Muhammad, but also through ritual leadership, collective recognition, inherited religious roles, and symbolic practices embedded in everyday social life. Weber’s concept of traditional legitimacy explains the collective acceptance of Sayyid authority, while Bourdieu’s concepts of symbolic capital, habitus, and field reveal how such legitimacy is continuously reproduced through social and religious practices. This study concludes that Sayyid legitimacy in Cikoang operates as a socially reproduced symbolic order maintained through ritual continuity, symbolic recognition, and community belief. These findings offer a synthesis between Weber's traditional legitimacy and Bourdieu's symbolic capital to explain the reproduction of spiritual authority beyond formal structures of power.